Sirolimus based therapy in live-donor renal transplantation: A prospective randomized study - Hamdy, Ahmed F; El-Agroudy, Amgad E; Bahgat, Sameh; Galal, Hasan; Mohsen, Tarek; Bakr, Mohamed A; El-Shahawy, El-Metwaly; Ghoneim, Mohamed A (African Journal of Nephrology, 2023)
Background/Aim: Calcineurin inhibitor nephrotoxicity has been one of the major clinical problems in clinical practice after renal transplantation. This study was conducted assuming that the advent of novel, potent and non-nephrotoxic immunosuppressant, sirolimus may counterbalance the calcineurin inhibitor dose reduction or avoidance to guard against nephrotoxicity. Methods: Between May 2001 and June 2002, 80 live donor renal allotransplant recipients were subjected to a prospective, randomized controlled trial where they were divided into two equal demographically matched groups to receive either low dose tacrolimus (0.03 mg/kg/day) Group A or mycophenolate mofetil (MMF 2 gm/day) { Group B} in combination with sirolimus (5 and 10 mg/day in group A and B respectively). All patients received steroids, according to local protocol, and basiliximab induction therapy. One year follow up for all patients was carried out including histological evaluation of renal allograft tissue at the end of first year. Results: One-year patient and graft survival rates were not significantly different between group A (97.5%, 94.6%) and group B (100%, 97.4%) respectively. However, group B patients experienced lower incidence of biopsy proven acute rejection, albeit statistically insignificant, being 10% in group B and 25% in group A. Moreover, group B patients demonstrated better renal allograft function as measured by serum creatinine at all studied time points. In addition, 1-year protocol biopsies showed significant lower incidence of tubular atrophy and interstitial fibrosis among group B patients. Conclusion: The present study demonstrates that excellent one year kidney transplant outcome can be achieved by sirolimus administration, especially with avoidance of calcineurin inhibitors.